A Metodologia de Trabalho de Projecto no 1º Ciclo do Ensino Básico. Porquê e Como? Conceções teóricas e práticas de docentes - Freitas, Ana Cristina (2020)
We have been gradually assisting in the defense of a meaningful, contextualized, functional curriculum and more open, with a view to school success and integral education. The Problem Based Learning (PBL) seems to respond to these challenges, because it promotes teaching-learning focused on solving problems, interests and learning needs of students, in an integrated, democratic and cooperative view of learning. However, the use of PBL in the 1st Cycle of Basic Education (1st CBE) is still scarce and considered by many teachers as difficult to execute. The present study tries to emphasize the contributions of the PBL to the teaching and learning of the 1st. CBE and essential aspects that are put in the use of this methodology, through the perceptions of teachers who use it in their pedagogical practice. A qualitative approach was adopted in the study and data were collected through semi directives interviews with 6 professors from the 1st. CBE, from private schools, about their pedagogical experiences with PBL. Data were subjected to content analysis. The results highlight the great contribution of PBL to the acquisition of essential skills for integral training, in particular: the promotion of autonomy; the development of critical capacity and reflection; and an increase in students' interest and motivation in their learning. As main difficulties experienced in carrying out project work, it was highlighted: the management of time; monitoring the work of all groups at the same time; the management of interests and conflicts; scarcity of resources; and evaluation of learning. The results also suggest that the low utilization of PBL in schools of the 1st. CBE is, mainly, due to the lack of openness and flexibility of the national curriculum and the lack of motivation and receptivity of schools and teachers for this curricular approach. It is suggested the extension of this study to other schools in the country, private and public education, the involvement of teachers with a different profile and still the families of the students involved in the PBL.